Understanding the roles of positive school culture and climate in supporting students’ wellbeing in vocational schools - Bentsalo, Inna; Ümarik, Meril; Loogma, Krista; Väljataga, Terje (Frontiers in Education, 2025)
This qualitative study investigates how vocational teachers and support staff in Estonia perceive their roles in promoting student well-being. Through group interviews with 16 participants from vocational schools across the country, thematic analysis was conducted. During the analysis, patterns emerged that were closely linked to the aspects of school culture and climate. School culture is conceptualized as shared values and traditions, while school climate encompasses the everyday experiences of communication, emotional safety, and school atmosphere. A conceptual framework is used to illustrate how culture and climate may jointly influence students’ well-being. The findings reveal variations in how students’ well-being is supported across vocational schools, often shaped by institutional leadership, organizational fragmentation, and informal role expectations. Limited engagement from school leadership and poor internal communication were frequently reported, suggesting that staff often act in isolation without systemic support. These findings highlight the need for coordinated school-wide approaches to well-being that move beyond individual initiatives. The study underscores the importance of cultivating stronger institutional responsibility and leadership, as well as fostering a positive school culture in vocational education settings.